1962
DOI: 10.1002/jctb.5010120803
|View full text |Cite
|
Sign up to set email alerts
|

Road building in the tropics

Abstract: The features of the different types of surfaced and unsurfaced road used in tropical countries are described, and an indication is given of some of the typical engineering features of tropical soils, using the ‘red coffee’ soil of Kenya as an example.Natural gravels are used extensivly in road building in tropical countries and the different types of gravel are describedSoil stabilisation is increasingly used to make road bases, and notes are given on the different processes employed. The paper concludes with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0
2

Year Published

1989
1989
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 3 publications
1
8
0
2
Order By: Relevance
“…The nature and relative importance of each of those "soil forming factors" varies in time and space. As far back as the eighteenth century, geologists identified that in warm, moist, temperate and tropical climates water percolating through rock has a strong weathering action (Millard 1993). Chemical reactions increase with an increase in rainfall and temperature, and accordingly soils from the tropics exhibit different engineering properties (Millard 1993).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The nature and relative importance of each of those "soil forming factors" varies in time and space. As far back as the eighteenth century, geologists identified that in warm, moist, temperate and tropical climates water percolating through rock has a strong weathering action (Millard 1993). Chemical reactions increase with an increase in rainfall and temperature, and accordingly soils from the tropics exhibit different engineering properties (Millard 1993).…”
Section: Introductionmentioning
confidence: 99%
“…As far back as the eighteenth century, geologists identified that in warm, moist, temperate and tropical climates water percolating through rock has a strong weathering action (Millard 1993). Chemical reactions increase with an increase in rainfall and temperature, and accordingly soils from the tropics exhibit different engineering properties (Millard 1993). Despite the great effort that has been made by previous works to classify and differentiate tropical soils, a uniform nomenclature /classification system does not exist yet for these soils.…”
Section: Introductionmentioning
confidence: 99%
“…Incessant occurrence of road pavement deterioration and building collapse, mainly because of their poor geotechnical and mechanical properties has made it imperative for a proper understanding of the geotechnical properties of soils (Garg, 2009). As far back as the eighteenth century, geologists identified that in warm, moist, temperate and tropical climates, water percolating through rock has a strong weathering action (Millard, 1993).…”
mentioning
confidence: 99%
“…Figura 2.24: Sensores láser para medida de la textura (Millard 1993) Figura 2.25. Profundidad media del perfil, MPD, (Millard 1993) Otros equipos determinan otros valores estadísticos, como el RMS, (Root Mean Square)…”
Section: Texturómetros Láserunclassified
“…Profundidad media del perfil, MPD, (Millard 1993) Otros equipos determinan otros valores estadísticos, como el RMS, (Root Mean Square)…”
Section: Texturómetros Láserunclassified